2017
DOI: 10.3390/rs9060635
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Interannual Variability of Columbia Glacier, Alaska (2011–2016): Ice Velocity, Mass Flux, Surface Elevation and Front Position

Abstract: Alaskan glaciers are among the largest contributors to sea-level rise outside the polar ice sheets. The contributions include dynamic discharge from marine-terminating glaciers which depends on the seasonally variable ice velocity. Columbia Glacier is a large marine-terminating glacier located in Southcentral Alaska that has been exhibiting pronounced retreat since the early 1980s. Since 2010, the glacier has split into two branches, the main branch and the west branch. We derived a 5-year record of surface ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…(36) during 2009 to 2013. A link between ice front changes and ice velocities is documented in a number of previous studies (Bevan et al, 2012, Howat et al, 2008, Moon et al, 2014, Vijay & Braun, 2017, and our work further supports this connection. A link between ice front changes and ice velocities is documented in a number of previous studies (Bevan et al, 2012, Howat et al, 2008, Moon et al, 2014, Vijay & Braun, 2017, and our work further supports this connection.…”
Section: Discussionsupporting
confidence: 88%
“…(36) during 2009 to 2013. A link between ice front changes and ice velocities is documented in a number of previous studies (Bevan et al, 2012, Howat et al, 2008, Moon et al, 2014, Vijay & Braun, 2017, and our work further supports this connection. A link between ice front changes and ice velocities is documented in a number of previous studies (Bevan et al, 2012, Howat et al, 2008, Moon et al, 2014, Vijay & Braun, 2017, and our work further supports this connection.…”
Section: Discussionsupporting
confidence: 88%
“…Previous observations of Alaskan tidewater glacier speeds suggest that seasonal changes in surface meltwater production alter the subglacial drainage network and thus basal drag (Durkin et al, ; McNabb et al, ; Ritchie et al, ; Stearns et al, ). Using a similar TSX‐derived record of surface speeds from 2011 to 2016, Vijay and Braun () recently postulated that speed seasonality at Columbia and Post is driven primarily by the evolution of the subglacial drainage network. As in our analysis, they observed that flow speeds reach their seasonal maxima in spring, then rapidly decrease throughout the summer months, reaching their seasonal minima in late fall—typically November (Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…To extend the 1952–2012 record of Columbia Glacier terminus positions by McNabb and Hock (), which is derived from historical topographic maps and Landsat images, we manually digitized terminus positions from 2013 to 2016 in cloud‐free Landsat 7 and 8 panchromatic images. Terminus positions could also be delineated from the available TerraSAR‐X and TanDEM‐X SAR imagery, as in Vijay and Braun (). A comparison of 2012 and 2013 terminus position time series constructed from Landsat imagery and from TerraSAR‐X/TanDEM‐X SAR imagery indicates that the seasonal to interannual patterns of terminus position change of interest here are captured equally well by the two satellite platforms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2010 and 2013 the average ice flux into the fjord was measured at 2.23 km 3 yr -1 (Pfeffer, 2013b), most of which came from the main branch of the glacier. Between 2011 and 2014 the average mass flux from the main branch of Columbia Glacier was measured to be 1.18 ± 0.30 Gt yr -1 (~1.29 km 3 yr -1 ) (Vijay and Braun, 2017). 5…”
Section: Introductionmentioning
confidence: 99%